2010
DOI: 10.1080/09540121003607241
|View full text |Cite
|
Sign up to set email alerts
|

Negotiating multiple barriers: health workers' access to counselling, testing and treatment in Malawi

Abstract: Malawi is facing a severe HIV and AIDS epidemic with an estimated 12% of its population living with the virus. Health workers are on the front lines of the HIV epidemic and they face the risk of HIV infection in both their personal and professional lives. This mixed method study aimed to explore the enablers and barriers to HIV counselling and testing and antiretroviral therapy by health workers in Malawi. After qualitative data were collected through in-depth interviews with health workers in the Mchinji and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
25
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 10 publications
5
25
1
Order By: Relevance
“…The impact of stigma on uptake of HIV testing has been reported in other studies [6, 11, 17, 32, 38]. In this study, fear of enacted stigma [39] was not found to be a barrier to HIV testing, even after probing for its influence.…”
Section: Discussionsupporting
confidence: 59%
“…The impact of stigma on uptake of HIV testing has been reported in other studies [6, 11, 17, 32, 38]. In this study, fear of enacted stigma [39] was not found to be a barrier to HIV testing, even after probing for its influence.…”
Section: Discussionsupporting
confidence: 59%
“…Researchers have documented that distance and limited health resources contribute to poor health care utilization in Malawi (Kambala et al, 2011; Namakhoma et al, 2010). To date, Malawi has had difficulty providing cervical cancer screening and treatment services (Fort et al, 2011; Taulo, 2008); however, HPV vaccination offers a promising solution, because widespread vaccine programs have already demonstrated to be successful within the context of Malawi.…”
Section: Discussionmentioning
confidence: 99%
“…Physical deterioration of health [30,32,37,39,40,43,46,48],[55,67,69] and poor health/death of sexual partner or child [31,43,48,59,68] elevated the perceived risk of infection and a decision to test:…”
Section: Resultsmentioning
confidence: 99%
“…In other instances, HIV testing was undertaken as an essential part of preparation for marriage [31,39,40,42,46,50,58,61]. For instance, a study in Ghana [50] encapsulates the role that the church was playing in increasing the uptake of HIV testing as an integral part of marriage preparation and counselling.…”
Section: Resultsmentioning
confidence: 99%